Rectal intussusception and external rectal prolapse are common at proctography in patients with mucus discharge - Tsunoda, Akira (J Anus Rectum Colon, 2018)
Objectives: Although various pelvic floor abnormalities are recognized to cause mucus discharge (MD), little is known about the exact distribution and frequency of diseases causing MD in evacuatory disorders. This study aimed to identify the most common diseases at evacuation proctography in patients with MD. Methods: Patients seen with symptoms of evacuatory disorder underwent proctography. Data for patients with MD who were not associated with fecal incontinence (FI) were prospectively entered into a database and analyzed retrospectively. The degree of MD was documented using FI Severity Index. Results: Sixty-two patients were included for analysis. Forty-nine (79%) had rectal intussusception (RI) or external rectal prolapse (ERP). Of those with RI, MD was observed more in patients with recto-anal intussusception (n = 22) than those with recto-rectal intussusception (n = 8). Of the 39 patients who were not associated with hemorrhoids or mucosal prolapse, 31 (79%) had RI or ERP. Meanwhile, of 582 patients who underwent proctography, 301 had RI and 96 had ERP. MD without FI was present in 13% (40/301) patients with RI and 9% (9/96) with ERP. Surgery was performed in 21 patients, and MD was cured in 20 (95%) postoperatively. Conclusions: RI and ERP were common at proctography in patients with MD.